Faktor-Faktor yang Memengaruhi Penerapan Payback Period sebagai Teknik Penganggaran Modal pada UMKM di Kota Bogor - Annisa Fathia Nurfitriani; Rindah Febriana Suryawati (Jurnal Manajemen dan Organisasi, 2017)
Micro, Small, and Medium Entreprises (MSMEs) are found to still have weak management and internal control system (Campbell and Hartcher 2013). The weak management system among others is in terms of decision-making related to the purchase of fixed assets in th business (Hidayah dan Ningsih 2015). So, MSMEs are difficult to apply capital budgeting techniques, including the simplest techniques which is payback period (Hasan 2013). The purpose of this study are to analyze the application of payback period as capital budgeting techniques in Bogor City MSMEs and to analyze factors that affecting it. Data analysis used in this research is logistic regression analysis. The result of this research shows that factors affecting the implementation of payback period in Bogor City MSMEs are small and medium business size, food and beverage business sector, and owner’s education level above high school, while business ownership, education level equal to high school, and trade business sector doesn’t affecting the implementation of payback period in Bogor City MSMEs.